PENINGKATAN BERPIKIR KRITIS DAN HASIL BELAJAR IPS MELALUI PROJECT BASED LEARNING BERBANTUAN GALLERY WALK - Purwaningsih; Sudarmiani; Hartono, Yudi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effectiveness of implementing Project Based Learning (PjBL) combined with the Gallery Walk technique in improving critical thinking skills and Social Studies (IPS) learning outcomes among students of class IXE at SMP Negeri 1 Madiun (n = 32). Using a Classroom Action Research design based on the Kemmis & McTaggart model with two cycles, the study collected data through observations using a critical thinking rubric, HOTS‑based learning outcome tests, in‑depth interviews, and documentation of student products such as posters and infographics. Quantitative results show an increase in the class mean score from 72.38 in Cycle I to 79.75 in Cycle II, while the classical mastery rate rose from 31.25% to 87.50%; statistical analysis indicated a significant difference (p < 0.001) with a large effect size. Qualitative findings corroborate the quantitative results, indicating that the Gallery Walk strengthened peer‑feedback mechanisms, encouraged product revision, and increased student participation and cognitive engagement. In conclusion, the combination of PjBL and Gallery Walk is effective in enhancing critical thinking and IPS learning outcomes, although strengthening self‑regulation and providing targeted remediation are needed to ensure that improvements are experienced more evenly across all students.